Implementation of Systematic Community Resource Referrals at Small Primary Care Practices to Promote Cardiovascular Disease Self-Management. Issue 5 (September 2020) - Makelarski, Jennifer A.; DePumpo, Megan; Boyd, Kelly; Brown, Tiffany; Kho, Abel; Navalkha, Chenab; Lindau, Stacy T.
Abstract : ABSTRACT: Quality improvement (QI) models and evidence-based self-management guidelines for reducing cardiovascular disease (CVD) risk require patients to access community resources. The purpose of this study is to describe outcomes from implementation of a community resource referral system into small clinical practices to reduce CVD risk. Practices were given the opportunity to complete an inventory of local CVD-related resources; these data were used to create a printed list of resources for patients ("HealtheRx-H3"). Practices could request updates to HealtheRx-H3s. We assessed implementation outcomes, including appropriateness, feasibility, and adoption. Practice populations were at high risk for CVD. It was feasible to create practice-specific HealtheRx-H3s. Systematic distribution of HealtheRx-H3s using digital electronic health record (EHR) integration was infeasible due to inconsistent use of EHR systems, workflow variation, and lacking data-sharing infrastructure. Of 76 practices, 38 completed the inventory; completion was similar by patient and practice characteristics. HealtheRx-H3 updates were requested by 39% of practices; practices that completed the inventory were significantly more likely to request an update compared with those that did not (61% vs. 18%, p -value <.01). Successful implementation of QI strategies to systematize community resource referral solutions is feasible at small practices, but more research is needed to understand what motivates small practices to participate in implementation of these solutions.